## bin+lib subscript-compiler

A modern LaTeX rendition

### 19 breaking releases

 0.21.0 Jul 19, 2021 Jul 1, 2021

#807 in Text processing

89KB
2.5K SLoC

# Work in progress...

Not yet ready for public consumption; please check back in a couple of months.

Ideally this will be usable for school this coming fall.

## Example

The end result of the following example will be similar to what you see over here.

...

\note[boxed] {
\h3{Symmetric Equation of a Line}
Given
\equation {
t &= \frac{x - x_1}{x_2-x_1} = \frac{x - x_1}{\Delta_x}\\
t &= \frac{y - y_1}{y_2-y_1} = \frac{y - y_1}{\Delta_y}\\
t &= \frac{z - z_1}{z_2-z_1} = \frac{z - z_1}{\Delta_z}
}
Therefore
\equation {
\frac{x - x_1}{Delta_x}
&= \frac{y - y_1}{\Delta_y}
= \frac{z - z_1}{\Delta_z}\\
\frac{x - x_1}{x_2-x_1}
&= \frac{y - y_1}{y_2-y_1}
=  \frac{z - z_1}{z_2-z_1}
}
\hr
\h4{Rationale}
We rewrite \{r = r_0 + a = r_0 + t v} in terms of \{t}.
That is
\equation{
x &= x_1 + t(x_2-x_1) = x_1 + t\;Delta_x\\
t\;Delta_x  &= x - x_1 = t(x_2-x_1)\\
t &= \frac{x - x_1}{x_2-x_1} = \frac{x - x_1}{Delta_x} \\\\
y &= y_1 + t(y_2-y_1) = y_1 + t\;\Delta_y\\
t\;\Delta_y  &= y - y_1 = t(y_2-y_1)\\
t &= \frac{y - y_1}{y_2-y_1} = \frac{y - y_1}{\Delta_y} \\\\
z &= z_1 + t(z_2-z_1) = z_1 + t\;\Delta_z\\
t\;\Delta_z &= z - z_1 = t(z_2-z_1) \\
t &= \frac{z - z_1}{z_2-z_1} = \frac{z - z_1}{\Delta_z}
}
}
\!where {
{\Delta_x} => {\colorA{\Delta_x}}
{\Delta_y} => {\colorA{\Delta_y}}
{\Delta_z} => {\colorA{\Delta_z}}
{x_1} => {\colorB{x_1}}
{y_1} => {\colorB{y_1}}
{z_1} => {\colorB{z_1}}
}


~2–2.7MB
~53K SLoC